Staphylococcal Superantigen-Like Protein 5 Inhibits Matrix Metalloproteinase 9 from Human Neutrophils - Itoh, Saotomo (American Society for Microbiology (ASM), 2010)
Staphylococcal superantigen-like proteins (SSLs) constitute a family of exoproteins exhibiting structural similarities to superantigens and enterotoxins but no superantigenic activity. In this article, we present evidence that SSL5 specifically binds to matrix metalloproteinase 9 (MMP-9) and inhibits its enzymatic activity. When human neutrophil cell lysate was applied to recombinant His-tagged SSL5 conjugated to Sepharose, the bound fraction gave a major band of approximately 100 kDa in SDS-polyacrylamide gel electrophoresis. This protein was identified as the proform of MMP-9 (proMMP-9) by peptide mass fingerprinting analysis. The recombinant SSL5-Sepharose also bound to proMMP-9 secreted by interleukin 8 (IL-8)-stimulated neutrophils and HT1080 fibrosarcoma cells. Surface plasmon resonance analysis revealed that recombinant SSL5 bound to proMMP-9 with rather high affinity (dissociation constant [K(D)] = 1.9 nM). Recombinant SSL5 was found to effectively inhibit MMP-9-catalyzed hydrolysis of gelatin and a synthetic fluorogenic peptide in a noncompetitive manner (K(i) = 0.097 nM), as assessed by zymography and the fluorescence quenching method. Finally, the transmigration of neutrophils across Matrigel basement membranes in response to N-formyl-methionyl-leucyl-phenylalanine (FMLP) was suppressed by the presence of recombinant SSL5. We discuss possible roles that SSL5 may play in immune evasion of staphylococci by inhibiting MMP and interfering with leukocyte trafficking.